Post breeding peritonitis in a Boxer bitch with ovarian remnant syndrome (ORS) - Almeida Biscarde, Carmo Emanuel [UNESP]; Dias Maziero, Rosiara Rosaria [UNESP]; Prestes, Nereu Carlos [UNESP]; Costa Mattos, Maria Clara [UNESP]; Monteiro, Gabriel Augusto [UNESP]; Pereira Stelmann, Ulisses Jorge [UNESP]; Marques Araujo, Gustavo Henrique [UNESP]; Bicudo, Sony Dimas [UNESP] (Univ Fed Rio Grande Do Sul, 2009)
The ovarian remnant syndrome (ORS) is defined as the persistence of ovarian activity in surgically spayed females, in which part or the entire ovary remains after the surgical procedure. ORS is characterized as a neo-vascular formation that promotes the organ's functions again, and may occur in cats and dogs. This condition causes the return of all undesirable signs of estrus, like male attraction, vaginal secretion (proestral bleeding), anxiety, pseudocyesis, among other symptoms. The recommended treatment is the surgical removal of the remaining ovary tissue. However, this procedure should be performed at the estrogenic stage of the cycle, when the remaining ovary tissue is enlarged due to the presence of follicles, which facilitates its location. Apparently there are no papers on the consequences of an undesirable breeding. Thus, the objective of this article was to report a case of peritonitis in a bitch with ORS after natural breeding, referred to the Hospital Veterinario da Faculdade de Medicina Veterinaria e Zootecnia da UNESP, campus Botucatu, Sao Paulo, Brazil.
Keywords: ovarian remnant syndrome (ORS); peritonitis; bitch